Investigating Pt/Pumice catalyst for efficient 3-methyl-1-butanol conversion - Paputungan, Mardjan; La Kilo, Akram (Acta Chimica Asiana, 2024)
The objective of this study was to obtain a modified Pt/pumice catalyst to support the conversion reaction of 3-methyl-1-butanol under specific reaction conditions. To achieve this objective, the first step involved preparing modified pumice catalyst pellets by impregnating them with Pt metal followed by activation at a temperature of 500 °C. The second step involved characterizing the Pt/pumice catalyst, including the surface distribution of Pt metal using SEM. The third step involved conducting the catalyst activity test against 3-methyl-1-butanol in a reactor (furnace) at temperatures ranging from 400 to 500°C with a flow system for the feed. The fourth step involved analyzing the conversion results using GC-MS chromatograms. The research results showed that the Si/Al ratio in the modified Pt/Pumice catalyst using a PtCl4 solution with a concentration of 0.0321 M for impregnation was 4:1, compared to 4.8:1 for Pt/Zeolite and 3.2:1 for Pt/ABP. The modified catalyst activity test for 3-methyl-1-butanol showed the following conversion results: Pt/Pumice 27.63%, Pt/Zeolite 23.85%, Pt/Black Pumice 14.81%, and for platinum catalyst, the conversion was 22.35%. These results indicated that the highest conversion was observed in the treated sample A-3 under the reaction condition of 450°C. The conversion products analyzed using GC-MS showed the presence of three molecules: 3-methylbutanal, 2-methylbutanal, and anhydrous isobutanoate.